Specificity of Problem-Solving Skills Training in Mothers of Children Newly Diagnosed With Cancer: Results of a Multisite Randomized Clinical Trial - Sahler, Olle Jane Z. (American Society of Clinical Oncology, 2013)
PURPOSE: Diagnosis of cancer in a child can be extremely stressful for parents. Bright IDEAS, a problem-solving skills training (PSST) intervention, has been shown to decrease negative affectivity (anxiety, depression, post-traumatic stress symptoms) in mothers of newly diagnosed patients. This study was designed to determine the specificity of PSST by examining its direct and indirect (eg, social support) effects compared with a nondirective support (NDS) intervention. PATIENTS AND METHODS: This randomized clinical trial included 309 English- or Spanish-speaking mothers of children diagnosed 2 to 16 weeks before recruitment. Participants completed assessments prerandomization (T1), immediately postintervention (T2), and at 3-month follow-up (T3). Both PSST and NDS consisted of eight weekly 1-hour individual sessions. Outcomes included measures of problem-solving skill and negative affectivity. RESULTS: There were no significant between-group differences at baseline (T1). Except for level of problem-solving skill, which was directly taught in the PSST arm, outcome measures improved equally in both groups immediately postintervention (T2). However, at the 3-month follow-up (T3), mothers in the PSST group continued to show significant improvements in mood, anxiety, and post-traumatic stress; mothers in the NDS group showed no further significant gains. CONCLUSION: PSST is an effective and specific intervention whose beneficial effects continue to grow after the intervention ends. In contrast, NDS is an effective intervention while it is being administered, but its benefits plateau when active support is removed. Therefore, teaching coping skills at diagnosis has the potential to facilitate family resilience over the entire course of treatment.